The Palgrave handbook of family sociology in Europe - Castrén, Anna-Maija; Česnuitytė, Vida; Crespi, Isabella 1971-; Gauthier, Jacques-Antoine; Gouveia, Rita; Martin, Claude; Moreno Mínguez, Almudena; Suwada, Katarzyna (Palgrave Macmillan, 2021)
1. Introduction -- 2. The Family of Individuals: An overview of the sociology of family in Europe, 130 years after Durkheim's first university course -- 3. Gender, social class and family relations in different life stages in Europe -- 4. What Law Has Joined: family relations and categories of kinship in the European court of Human rights -- 5. Family demography and values in Europe: Continuity and change -- 6. The configurational approach to families: Methodological suggestions -- 7. Visual Family Research Methods -- 8. Family transformations and sub-replacement fertility in Europe -- 9. Reexamining Degenderization. Changes in Family Policies in Europe -- 10. Familialisation of Care in European Societies. Between family and the state -- 11. Who Benefits from Parental Leave Policies? A Comparison Between Nordic and Southern European Countries -- 12. Family, poverty, and social policy interventions -- 13. Redefining the boundaries of family and personal relationships --
Keywords: Familiensoziologie; Social groups; Family; Social policy; Welfare state; Social service